The Effectiveness of Using Google Earth to Improve the Spatial Skills of Phase B Elementary School Students - Siti Maemunah; Sendi Fauzi Giwangsa; Mubarok Somantri (LP2M STIT Palapa Nusantara, 2025)
This study addresses the issue of low spatial abilities among Phase B elementary school students, particularly in understanding regional location, spatial orientation, and distance. The problem is attributed to the continued use of conventional learning media that lack the capacity to visualize spatial concepts in an engaging and concrete manner. The research aims to evaluate the effectiveness of Google Earth as a digital learning medium to enhance students’ spatial abilities within the IPAS subject, specifically on the topic of identifying the location of their city or regency. A quantitative research approach was employed using a pre-experimental one-group pretest-posttest design. The participants comprised 25 fourth-grade students from SDN Cisarua, West Bandung Regency. Data were collected using an essay test consisting of 10 questions. The results showed a significant increase in posttest scores compared to pretest scores, with the N-Gain categorized as high. Statistical analysis further confirmed a significant difference between pretest and posttest performance. The study concludes that the integration of Google Earth is effective in improving spatial abilities among elementary school students. These findings support the use of interactive, contextual, and technology-based learning tools as viable alternatives to traditional methods in enhancing geography-related competencies in early education.